Mechanical, Thermal, and Morphological Characterization of Polyethylene Glycol–Modified Epoxy Composites - Karataş, Mukaddes; Aydoğmuş, Ercan; Erzen, Buket; Orhan, Ramazan (Turkish Chemical Society, 2026)
Abstract : Polyethylene glycol (PEG) has emerged as a promising modifier for enhancing the toughness and thermomechanical performance of epoxy-based materials. However, the combined influence of PEG incorporation on the mechanical, thermal, and morphological behavior of epoxy composites has not yet been comprehensively clarified. In this study, epoxy composites reinforced with different PEG contents (3–18 wt.%) were successfully fabricated and systematically characterized to reveal the role of PEG in tailoring the multifunctional performance of epoxy systems. The composites were evaluated through bulk density, Shore D hardness, tensile testing, and thermal conductivity measurements, while Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) analyses were conducted to investigate structural interactions and fracture morphology. The results demonstrated that PEG incorporation significantly altered the physical and mechanical behavior of the epoxy matrix. Increasing PEG content reduced the Shore D hardness from 77.5 for neat epoxy to 65.7 at 18 wt.% PEG, indicating enhanced flexibility within the crosslinked network. In contrast, thermal conductivity increased markedly from 0.112 to 0.148 W·m⁻¹·K⁻¹ with increasing PEG concentration, demonstrating the beneficial role of PEG in promoting heat transfer through the polymer matrix. Tensile analysis revealed that the composite containing 10 wt.% PEG exhibited the most balanced mechanical performance, achieving an ultimate tensile strength of approximately 60–61 MPa together with a significantly increased strain at failure of 3.5–3.7%, indicating improved ductility and toughness without substantial strength loss. FTIR results confirmed that PEG modified the epoxy matrix primarily through physical interactions rather than chemical bonding, while SEM observations revealed enhanced plastic deformation and energy absorption mechanisms. These findings provide new insight into the multifunctional role of PEG as a flexible performance modifier and demonstrate its potential for designing epoxy composites with simultaneously improved toughness and thermal transport properties for advanced engineering applications.
Keywords: Epoxy composite; polyethylene glycol; mechanical properties; thermal properties; characterization.